Perancangan Alat Peraga Medan Magnet Disekitar Kawat Berarus dengan Hall Magnetik Sensor Bipolar Analog sebagai Demonstrasi dalam Pembelajaran Fisika - Melisa Putri Febriyanti; Alex Harijanto; Subiki .; Nidya Mashitoh; Tika Ningrum; Evie Rahmawati; Ratna Anindy (Jurnal Ilmiah Wahana Pendidikan, 2023)
Magnetic field props not only help students in understanding the basic concepts of magnetic fields, but also help in proving the existence of magnetic fields in electric current wires. The magnetic field practicum tool around the current wire, with that tool, students can conduct experiments to prove the existence of a magnetic field around the current wire and observe the direction of the deviation that occurs. The research method used is quantitative descriptive method. The collected data in a quantitative descriptive manner is used to provide an overview of the actual situation, as well as to answer questions related to the status of the subject of the study. The experiment was carried out by changing the voltage value, namely at 1.5V and 3V to analyze the difference. The relationship between the magnitude of the voltage V to the strength of the current I is directly proportional. That is, the greater the voltage given, the greater the current generated, and vice versa. Then the relationship between the strength of current I to the magnitude of deviation B is directly proportional. That is, the greater the strong current produced, the greater the deviation produced, and vice versa.